2008
DOI: 10.1093/humrep/den051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of surface markers for prospective isolation of human endometrial stromal colony-forming cells

Abstract: This study identified CD146 as a marker of colony-forming human endometrial stromal cells supporting the concept that human endometrium contains a population of candidate stromal stem/progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
119
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(132 citation statements)
references
References 52 publications
9
119
0
4
Order By: Relevance
“…More recently, they were also found in the human uterus endometrium and in menstrual blood and have been shown capable of promoting regeneration in vivo [16,18,19,21,22,32,33]. A recent study demonstrated isolating stem cells from the endometrium and promoting in vitro chondrogenesis [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, they were also found in the human uterus endometrium and in menstrual blood and have been shown capable of promoting regeneration in vivo [16,18,19,21,22,32,33]. A recent study demonstrated isolating stem cells from the endometrium and promoting in vitro chondrogenesis [20].…”
Section: Discussionmentioning
confidence: 99%
“…The extraordinary regenerative capacity of the human endometrium following menstruation, in the postpartum period, after surgical procedures (uterine curettage, endometrial ablation) and in postmenopausal women undergoing hormonal replacement therapy suggests that MSC niches present in this tissue could be responsible for this process [16]. Indeed, endometrial and menstrual blood-derived stem cells were recently isolated and showed the ability to differentiate into cell types of the three germ layers [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Several markers for stem cells in human uterus have been identified; however, these markers are not highly specific for endometrial stem cells (Schwab et al 2008). In the endometrium, the most commonly mentioned markers, indicating stem cell properties are cell membrane antigen C-KIT, also known as CD117, and intracellular transcription factor OCT3/4.…”
Section: Introductionmentioning
confidence: 99%
“…In the endometrium, the most commonly mentioned markers, indicating stem cell properties are cell membrane antigen C-KIT, also known as CD117, and intracellular transcription factor OCT3/4. The C-KIT marker is usually associated with hematopoietic stem cells and its expression may suggest a medullary origin of these stem cells (Cho et al 2004, Schwab et al 2008. Moreover, identification of two other nuclear transcription factors, NANOG and SOX2, allows for determining the presence of stem cells in the uterus.…”
Section: Introductionmentioning
confidence: 99%
“…Somatic stem cells (SCs) are a subset of cells residing in normal adult tissues that, through asymmetric division, retain their ability to self-renew while producing daughter cells that go on to differentiate and play a role in regeneration and repair of the native host tissue [Ono et al 2012;Schwab et al 2008]. Thus their differentiation capacities are usually restricted to the tissue's derivatives of particular germ layer of their origin.…”
Section: Introductionmentioning
confidence: 99%